THE EFFECT of GA3 AND SALINITY on GROWTH of ROSELLE (Hibiscus sabdariffa L.) - Aisar Novita; Mohammad Basyuni; Abdul Rahman Cemda; Silvia Nora; Merlyn Mariana (International Journal of Biosciences and Biotechnology, 2021)
In order to alleviate the deleterious effects of salinity, different types of phytohormones have been used. Among them, GA3 has been the main focus of some plant scientists. This study aimed to evaluate the effect of gibberellic acid and salinity on growth and production of roselle (Hibiscus sabdariffa L). This research was conducted in a greenhouse of Agriculture Faculty, University of Sumatera Utara, Medan. The study used utterly randomized design with two factors. The first factor was gibberellic acids. They were gibberellic acid (5 mg L-1) and no gibberellic acid. The second factor was salinity. They were 0 dsm-1 and 4-5 dsm-1. The interaction between gibberellic acid and salinity acid indicated a significant effect on the percentage of germination, chlorophyll a and b and beta-carotene. The application of giberellic acid helped in the tolerance of plants to salinity. Thus, application of GA3 become essential to improve overall productivity in salinity.